KARAKTERISTIK FRAKTUR MAKSILOFASIAL DI RSUP DR. M. DJAMIL PADANG TAHUN 2014-2016 - Irma Oktavina Zulmi; Rima Semiarty; Angel Laura (Faculty of Dentistry Universitas Andalas, 2017)
Maxillofacial fractures or facial fractures are discontinuity of the facial bone. Maxillofacial fractures are the most common cause traffic accidents. RSUP. M. Djamil is the main referral hospital in the city. That can be found at RSUP. DR. M. Djamil Padang. To determine the characteristics of maxillofacial fractures in RSUP. M. D jamil Padang in 2014- 2016.The type of this research is Obsevational Descriptive by using a retrospective design, there are 78 samples takenmfrom medical records. As for the sampling technique, we use simple random sampling. This study was conducted with a sample based on the data group maxillofacial fractures based on the type of fracture, the patient’s age, gender, aetiology and treatment. Then, the tabulation and presentation of data using SPSS version 22.0. there are 78 patients from 350 patients who suffered maxillofacial fractures. The highest number of 27 patients (34,6%) had multiple fractures, 61 patients (78,2%) experienced by men, most in the age 11-20 years as many as 36 patients (46,2%), the highest caused by traffic accident 75 patients (96,2%), the most performed treatment was closed reduction 39 patients (50%).Traffic accidents are the leading cause of maxillofacial fractures. Based on the type of fractures more patients suffered multiple fractures being experienced at the age of 11-20 years. The most performed treatment was closed reduction. Keywords:Maxillofacial fractures, RSUP. Dr. M. Djamil Padang